2020
DOI: 10.12659/msm.920261
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes and Pathways in Gastric Adenocarcinoma Based on Bioinformatics Analysis

Abstract: Background:Gastric adenocarcinoma accounts for 95% of all gastric malignant tumors. The purpose of this research was to identify differentially expressed genes (DEGs) of gastric adenocarcinoma by use of bioinformatics methods. Material/Methods:The gene microarray datasets of GSE103236, GSE79973, and GSE29998 were imported from the GEO database, containing 70 gastric adenocarcinoma samples and 68 matched normal samples. Gene ontology (GO) and KEGG analysis were applied to screened DEGs; Cytoscape software was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…A previous study used bioinformatics to predict the DEGs of STAD and its enriched pathways and screened and evaluated some hub genes to provide some ideas and references for the early diagnosis and treatment of STAD at the molecular level. For example, upregulation of COL3A1 , COL1A2 , BGN , and THBS2 were found to significantly reduce the survival time of STAD patients ( Qiu et al, 2020 ). FN1 , SPARC , and SERPINE1 were highly expressed and significantly related to a poor prognosis of STAD ( Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study used bioinformatics to predict the DEGs of STAD and its enriched pathways and screened and evaluated some hub genes to provide some ideas and references for the early diagnosis and treatment of STAD at the molecular level. For example, upregulation of COL3A1 , COL1A2 , BGN , and THBS2 were found to significantly reduce the survival time of STAD patients ( Qiu et al, 2020 ). FN1 , SPARC , and SERPINE1 were highly expressed and significantly related to a poor prognosis of STAD ( Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our studies demonstrated that 6 genes ( COL1A1 , COL1A2 , COL2A1 , COL11A1 , THBS2 , and SPP1 ) were particularly enriched in ECM-receptor interaction or focal adhesion pathways. Qiu et al [ 41 ] also identified COL1A1 , COL1A2 , THBS2 , and SPP1 as being significantly overexpressed in GC tissues, and COL1A2 and THBS2 were associated with significantly reduced survival time in GC patients. The ECM mixture serves an important role in tissue and organ morphogenesis and the maintenance of cell and tissue structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al 37 Analyzed the gene bank of endometrial cancer and found that SPP1 gene was related to focal adhesion. Qiu et al 38 Analyzed the gene pool of gastric adenocarcinoma, and found that SPP1 gene was significantly up-regulated in gastric adenocarcinoma, which promoted the adhesion of gastric cancer cells and shortened the survival time of patients with gastric adenocarcinoma. These provide the directions for further study of SPP1 gene.…”
Section: Discussionmentioning
confidence: 99%